Persepsi Angela Merkel dan Open Door Policy dalam Krisis Pengungsi Eropa 2015 - Annisa Nabilatul Khaira; Muhammad Yusra; Rifki Dermawan (Parahyangan Center for International Studies, 2022)
When Europe was hit by the refugee crisis in 2015, Germany as the leader of the European Union implemented policies that contrasted markedly with those of other member countries. Through the Open Door Policy under the command of Angela Merkel, Germany voluntarily opened its borders so that refugees were able to enter its territory. Unfortunately, this policy triggered many protests and rejections from various circles. Among these were members of the general public, opposition parties, Merkel's own party, interest groups and the European Union as a regional umbrella for Germany. The determination of this policy did not involve the participation of the Bundestag (level I parliament) in a democratic manner, either. Despite the many objections that arose, Merkel remained adamant about defending and enforcing her controversial policy. This attitude reflects the existence of a separate perspective or perception that Merkel had in seeing the refugee crisis, so she established an Open Door Policy. This paper will shed light on how Angela Merkel's personal perception could have led to her choice of providing protection for refugees despite having to face various forms of resistance. By using the framework of the relationship between perception and decision-making according to Ole R. Holsti, it was found that belief and image systems influenced Angela Merkel's perception that Germany should be the main actor in responding to the refugee crisis that occurred in the European Union region and the rest of the world as well.